Los términos para el color verde y azul y su desarrollo semántico en la lengua asháninka y ashéninka - Solari Ruiz-Eldredge, Óscar Augusto (2020)
In this research, introduces the analysis of the chromatic terms that make up the category of green and blue colours is presented. Each one is the result of the codification of the perception of salient aspects of diverse referents of nature, which is evident in the opacity that shows its structure. The phenomena involved in their reconstruction are based on the theory of lexicalization and metonymy, and their belonging to the category through the theory of basic colours and prototypes. In the category of green, the term kenashiri is constructed from a phytonym; matsiriari and natsiriari, from the aspect of abnormal coloration in the skin, and eereki and eerepa, from the coloration of the fruits when they sprout. Likewise, in the category of blue, asoriri is a hispanism and kamachonkari is constructed from the perception of the appearance of an entity or its color with a low degree of brightness.